2001
DOI: 10.1080/00034980120092543
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate drug advice in the pharmacies of Guatemala and Mexico: the scale of the problem and explanatory factors

Abstract: A study of urban pharmacies in Guatemala and in Chiapas, southern Mexico, was undertaken to analyse the scale of the inadequate drug advice provided, and to identify the contributing factors. The estimate of the scale of the problem was based on the results of 969 approaches to 191 pharmacies by 'magic clients' (i.e. researchers pretending to be looking for treatment for relatives who had one of three 'tracer' diseases), interviews with 4469 pharmacy users as they left the same 191 pharmacies, and a comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 19 publications
0
38
0
2
Order By: Relevance
“…Special outreach efforts may be required by pharmacists to better serve Latino patients. Past research suggests that the medication advice given in pharmacies in some Latin American countries is poor [3]. This may explain, at least in part, why only 16.1% of study participants identified pharmacists as their preferred source of verbal medication information.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Special outreach efforts may be required by pharmacists to better serve Latino patients. Past research suggests that the medication advice given in pharmacies in some Latin American countries is poor [3]. This may explain, at least in part, why only 16.1% of study participants identified pharmacists as their preferred source of verbal medication information.…”
Section: Discussionmentioning
confidence: 86%
“…Cross-border purchasing of medicines is also a concern in other countries [8,9]. Some concerns with Latinos purchasing medications in ''tiendas'' or in other countries are: using harmful medications, using medicines incorrectly, and receiving inadequate medication information [3,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,24,32 Six studies came from African regions: Gambia, 33 Kenya, 29 South Africa, 41,45 Sudan, 36 and Zimbabwe, 35 Lastly, 11 studies were undertaken in Latin American and Caribbean regions: Bolivia, 25 Brazil, 34,38 Colombia, 43 Mexico, 20,21,31,42 Jamaica, 23 Latin American, 30 and both Guatemala and Mexico. 28 A wide variety of scenarios (n ¼ 64) were covered. This included abortifacients and/or misoprostol requests, 21 34 hypertension, 28 influenza remedies in hypertension, 43 malaria chemoprophylaxis, 41 metronidazole use in pregnancy, 43 migraine, 40 oral and/or emergency contraceptives, 20,23 sexually transmitted infections, 22,29,33,35,38,42,45 steroid requests, 32 and supplying dipyrone or misoprostol without prescription.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…28 A wide variety of scenarios (n ¼ 64) were covered. This included abortifacients and/or misoprostol requests, 21 34 hypertension, 28 influenza remedies in hypertension, 43 malaria chemoprophylaxis, 41 metronidazole use in pregnancy, 43 migraine, 40 oral and/or emergency contraceptives, 20,23 sexually transmitted infections, 22,29,33,35,38,42,45 steroid requests, 32 and supplying dipyrone or misoprostol without prescription. 43 Several methods were used to conduct these 28 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%